Variation in individual milk production responses to supplementary protein feeding with two types of forages - Sairanen, Auvo; Huhtanen, Pekka (Elsevier, 2024)
The objectives of the present experiment were to investigate the effects of forage type and protein supplementation on feed intake and milk production, and between-cow variability in responses to protein supplementation. The experiment was conducted using 40 cows (28 Holstein, 12 Nordic Red, 25 multiparous, 15 primiparous). Experiment started with a covariate period of 14 d when cows received TMR (concentrate:forage, 40:60). After the covariate period four experimental diets were arranged in 2 × 2 factorial design with two forages and two concentrate CP levels. The forage treatment included grass silage (GS) and a mixture of whole-crop wheat/oats silage and grass silage (MIX; 40:60) on DM basis. The concentrate treatment included two concentrate CP levels [low CP (115 g CP/kg DM) and medium CP (166 g CP/kg DM)]. Concentrate CP concentration was increased by replacing barley and oats with rapeseed meal. The cows were fed the same forage throughout the 63-d experiment, whereas the CP treatments were compared in a switch-back design including three 21 d periods. Individual protein supplementation response was calculated based on switch-back periods. Feeding the MIX forage increased total DM intake by 1.3 kg/d compared with the GS diets but milk production was not influenced by forage type. Dry matter and nutrient intake increased with CP level similarly with forages. The production of milk components and milk urea concentration increased with CP level, whereas milk N efficiency decreased. Energy corrected milk (ECM) yield response to protein supplementation was not related to ECM yield measured during the covariate period whereas the ECM response was negatively related to calculated energy balance during covariate period. It is concluded that intake and production responses to moderate level of protein supplementation were highly variable, but the extent of variation could not be predicted from animal characteristics available in farm conditions. When the supply of metabolizable protein (MP) was simulated by the Karoline model for each animal, predicted MP concentration increased 0.8 g/kg increase in DM intake. This is compatible to increased MP requirement on DM basis with enhanced production level. Both the lack of the effects of initial production level on CP response and the higher predicted MP concentration with increased intake suggest that high yielding cows can deal with the higher MP requirement (on DM basis) without increasing dietary CP concentration.
Keywords: dairy cow; nitrogen utilization; rapeseed meal; whole crop silage; grass silage; precision feeding